2014
DOI: 10.1186/2047-783x-19-13
|View full text |Cite
|
Sign up to set email alerts
|

Totally thoracoscopic repair of atrial septal defect reduces systemic inflammatory reaction and myocardial damage in initial patients

Abstract: BackgroundTo compare the effect of totally thoracoscopic with conventional, open repair of atrial septal defect.MethodsForty atrial septal defect cases were divided into two groups by surgical approach: totally thoracoscopic approach (group A, n = 20) and conventional open approach (group B, n = 20). In group A, surgical procedures were performed through three portal incisions in the right lateral chest wall under thoracoscopic vision without the aid of a computerized robotic surgical system. Notably, all oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Myocardial injury was the most prominent extrapulmonary complication, which was more common in MP-associated bronchiolitis than in RSV-associated bronchiolitis, and emergent MP-associated bronchiolitis can cause more harm. Several studies revealed that myocardial damage was related to changes in immune function caused by inflammation [ 29 31 ], and this is supported by the present study, which found C-reactive protein and procalcitonin levels were elevated in patients with MP-associated bronchiolitis.…”
Section: Discussionsupporting
confidence: 89%
“…Myocardial injury was the most prominent extrapulmonary complication, which was more common in MP-associated bronchiolitis than in RSV-associated bronchiolitis, and emergent MP-associated bronchiolitis can cause more harm. Several studies revealed that myocardial damage was related to changes in immune function caused by inflammation [ 29 31 ], and this is supported by the present study, which found C-reactive protein and procalcitonin levels were elevated in patients with MP-associated bronchiolitis.…”
Section: Discussionsupporting
confidence: 89%
“…Xiao et al reported a series of cases of total thoracoscopic closure of ASD on beating hearts with the da Vinci Surgical System (6). We previously reported that the total thoracoscopic ASD repair resulted in a lower level of systemic inflammatory response (SIRS) after CPB compared with conventional surgery through a sternotomy, including the level of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-10 (IL-10), and intercellular adhesion molecule 1 (ICAM-1), and reduced the damage to tissue and organs (9).…”
Section: Discussionmentioning
confidence: 99%
“…Total endoscopic repair of atrial septal defect under on-pump beating heart cardioplegia (9). Based on the previous reports (6,10-13), we improved the techniques and skills of the total endoscopic closure for ASD on beating hearts without the assistance of a robotic surgical system which made the procedure to be much more appropriate and feasible.…”
Section: Original Articlementioning
confidence: 99%
“…The totally video-assisted thoracoscopic procedure has been reported as a safe and effective method for repairing simple congenital heart defects with a rapid recovery of life quality and lower pain levels compared with both minithoracotomy and median sternotomy [15]. Meanwhile, lower systemic inflammatory reactions and myocardial damage were also observed after ASD repair with the method [16].…”
Section: Discussionmentioning
confidence: 99%